Macroscopic Anatomy of the Lower Respiratory System in Mole rats (Spalax leucodon) - Ilgun, R.; Yoldas, A.; Kuru, N.; Ozkan, Z. E. (Wiley, 2014)
The morphologic and morphometric features of the lower respiratory system in mole rats were examined. It was seen that the low respiratory system of this species leading a special life under highly hypoxic/hypercapnic conditions underground is structurally similar to other mammals living on land in terms of the parts examined; trachea was formed by 29.5 +/- 4 oval-formed cartilaginous tracheals arranged backwards and became gradually more stenotic diameter from cranial to the caudal of the neck. The trachea was separated in two principal bronchus at the fourth thoracal intercostal spatium level. The angle between the two main principal bronchi was 60.5 +/- 2.35 degrees. The lung constituted 1.29 +/- 0.03% of the body weight and the right lung was heavier than the left lung. Fissura inter-lobaris was deep and separated the lung lobes wholly, and the right lung was separated in four lobes, whereas the left lung was not separated into the lobes. Also, the medial lobe of the left lung was the lightest lobe.
Keywords: Bat Tadarida-Brasiliensis; Bronchial Tree; Lungs; Dog; Hemoglobin; Departures; Optimality; Ehrenbergi; Tolerance; Hypoxia